2010
DOI: 10.1093/jac/dkq269
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of the IncN plasmid pKOX105 encoding VIM-1, QnrS1 and SHV-12 proteins in Enterobacteriaceae from Bolzano, Italy compared with IncN plasmids encoding KPC enzymes in the USA

Abstract: IncN plasmids are broad host-range plasmids that have contributed significantly to the worldwide dissemination of many different resistance genes in Enterobacteriaceae from animal and human sources. This plasmid family is now playing a crucial role in the global spread of diverse carbapenemase genes in Klebsiella spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 12 publications
3
51
0
1
Order By: Relevance
“…In addition, combinations of fosfomycin with meropenem, colistin, and gentamicin prevented the development of resistance to fosfomycin in 69.2, 53.8, and 81.8% of examined isolates, respectively. Similar results were obtained by another study that demonstrated synergy of fosfomycin with imipenem, meropenem, doripenem, colistin, netilmicin, and tigecycline for 74,70,74,36,42, and 30% of 50 KPC-producing K. pneumoniae isolates, respectively (228).…”
Section: In Vitro Synergysupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, combinations of fosfomycin with meropenem, colistin, and gentamicin prevented the development of resistance to fosfomycin in 69.2, 53.8, and 81.8% of examined isolates, respectively. Similar results were obtained by another study that demonstrated synergy of fosfomycin with imipenem, meropenem, doripenem, colistin, netilmicin, and tigecycline for 74,70,74,36,42, and 30% of 50 KPC-producing K. pneumoniae isolates, respectively (228).…”
Section: In Vitro Synergysupporting
confidence: 87%
“…Indeed, insertion elements (ISs) such as IS26, ISEc33, ISSen4, and ISAba125, either alone or as parts of transposons (e.g., Tn3 and Tn1696), commonly flank M␤L-encoding regions (Fig. 1, structures II to VI) (42,59,114,165,167,215,218,273). At least some of the latter elements apparently participate in the spread of M␤L-encoding sequences among different genetic units.…”
Section: M␤lsmentioning
confidence: 99%
“…The same reading frame was also detected on the IncN plasmid R46 (NC_003292). Immediately upstream of this open reading frame, an incomplete reading frame for a protein was detected, of which the C-terminal 186 aa corresponded exactly to the Mrr protein of the IncN plasmid pKOX105 from Klebsiella oxytoca (7).…”
Section: Resultsmentioning
confidence: 99%
“…Whole-plasmid sequencing and comparative genomic analyses have identified common functional modules and unique acquired genes that provide important molecular information for developing epidemiological tools to identify and track the spread of resistance plasmids within and among Enterobacteriaceae species (17)(18)(19)(20). Various bla KPC-2 -and bla KPC-3 -harboring plasmids belonging to different Inc groups have been successfully sequenced, including IncN plasmids p9 and p12 (10), IncFII plasmids pKPHS2 (21), pKP048 (19), pKpQIL (20), pKpQIL-IT (18), and pSLMT (HQ589350), and ColE1 plasmid p15S (10).…”
mentioning
confidence: 99%